Just like being there [videorecording (DVD)] - Danger, Daniel; Ryan, Jay, 1981-; Tong, Kevin (Virgil Films, 2013)
In the gig poster community, artists such as Daniel Danger and Jay Ryan prove that creating this artwork is a way of life, more than just a career. These artists are at the forefront of an expansion of the gig poster genre. MONDO's reinvigoration of 'the film poster as an art form' and Gallery 1988's theme based exhibits are only two ways in which the artwork is reaching a greater public.